Anti-diabetic effects of excipients: possibility of formulation of an anti-diabetic dosage form using pharmaceutical excipients or their constituents, or food additives - Shireesh Apte (Journal of Excipients and Food Chemicals, 2016)
The ability of pharmaceutical excipients to exhibit significant bioactivity independent of the active pharmaceutical ingredient is beginning to be recognized. Certain types of diets or foods have been demonstrated to alleviate diabetic symptoms. Because most excipients are derivatives of food products, it is not unreasonable to assume that these molecules are responsible at least in part for the diabetes ameliorative properties of such foods or food products. Indeed, evidence has accumulated that such excipients act on well defined pharmacologic pathways and targets in order to exercise their beneficial effects. If excipients that act on multiple diabetogenic pharmacologic targets or pathways are combined together in concentrations that are at or above their recommended dietary allowances, the possibility exists that such a formulation may provide “stand alone” control of type II diabetes. The formulation could be as simple as a mixture of these solid powders presented in a ‘sachet’ or pack to be mixed with water and taken once or twice a day.